2002
DOI: 10.1055/s-2002-36203
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Guided Laser-Induced Interstitial Thermotherapy (SLITT) in Gliomas with Intraoperative Morphologic Monitoring in an Open MR: Clinical Expierence

Abstract: Stereotactic guided laser-induced interstitial thermotherapy (SLITT) is a minimal invasive method to produce thermonecrosis in cerebral tumour tissue. Clinical data are sparse due to its limited application until now and the value of this approach for tumour control and survival time remain to be defined. Twenty-four patients (7 low-grade gliomas, 11 anaplastic gliomas, 6 glioblastomas) with brain tumours, most recurrences, were treated with SLITT, in total 30 laser procedures were performed. Under local anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Leonardi and Lumenta report that the mean progressionfree survival for recurrent Grade III and IV HGGs was 10 and 4 months, respectively. 38 The mean overall survival for recurrent Grade III and IV HGGs was 30 and 9 months, respectively. 38 Schwarzmaier et al reported that the overall survival of 16 patients with recurrent HGG after LITT was 11.2 months.…”
Section: Stereotactic Laser Ablation As a Salvage Therapy For Recurrementioning
confidence: 97%
See 2 more Smart Citations
“…Leonardi and Lumenta report that the mean progressionfree survival for recurrent Grade III and IV HGGs was 10 and 4 months, respectively. 38 The mean overall survival for recurrent Grade III and IV HGGs was 30 and 9 months, respectively. 38 Schwarzmaier et al reported that the overall survival of 16 patients with recurrent HGG after LITT was 11.2 months.…”
Section: Stereotactic Laser Ablation As a Salvage Therapy For Recurrementioning
confidence: 97%
“…38 The mean overall survival for recurrent Grade III and IV HGGs was 30 and 9 months, respectively. 38 Schwarzmaier et al reported that the overall survival of 16 patients with recurrent HGG after LITT was 11.2 months. 65 Carpentier et al reported that overall survival among 4 patients with HGGs was 10 months after LITT.…”
Section: Stereotactic Laser Ablation As a Salvage Therapy For Recurrementioning
confidence: 97%
See 1 more Smart Citation
“…11,13,21,22 The minimally invasive nature of LITT coupled with advances in MR thermography techniques has led to the exploration of this technique's use for various neurosurgical indications such as deep-seated glioma, 8,9,20,22 brain metastasis, 2,5,21 radiation necrosis, 4,16,21 and epilepsy. 7,23 LITT has shown promising results in the management of patients with difficult-toaccess brain tumors 12 and has emerged as a potential tool in the armamentarium of neurosurgeons.…”
Section: Neurosurg Focus 41 (4):e6 2016mentioning
confidence: 99%
“…Four studies that evaluated LITT as salvage therapy for recurrent HGG reported an overall survival of 9-15 months posttreatment. 1,5,7,8 Although these promising data are similar to survival achieved with salvage surgery for HGG, it is impossible to control for the contribution of adjuvant chemotherapies to this outcome. Nevertheless, recurrence may represent a favorable context for LITT application, because patients in this cohort are often poor surgical candidates with focal disease.…”
mentioning
confidence: 94%